2018
DOI: 10.1016/j.nicl.2018.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Multi-component relaxation in clinically isolated syndrome: Lesion myelination may predict multiple sclerosis conversion

Abstract: We performed a longitudinal case-control study on patients with clinically isolated syndrome (CIS) with the aid of quantitative whole-brain myelin imaging. The aim was (1) to parse early myelin decay and to break down its distribution pattern, and (2) to identify an imaging biomarker of the conversion into clinically definite Multiple Sclerosis (MS) based on in vivo measurable changes of myelination.Imaging and clinical data were collected immediately after the onset of first neurological symptoms and follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Studies employing structural and diffusion-weighted MRI critically complement and extend the above-mentioned findings by directly measuring differences in brain structure. In line with the finding that breastfeeding impacts the timing of myelination, whole brain volume, cortical thickness, and white matter volume have all been found to be increased among children with longer durations of breastfeeding experience [ 33 , 37 39 ]. For example, in a cross-sectional design, Deoni et al [ 33 ] investigated white matter maturation from 10 months to 4 years of age and found a positive association between the duration of exclusive breastfeeding and the development of white matter tracts.…”
Section: Psychological Effects Of Breastfeeding In Childrenmentioning
confidence: 57%
See 2 more Smart Citations
“…Studies employing structural and diffusion-weighted MRI critically complement and extend the above-mentioned findings by directly measuring differences in brain structure. In line with the finding that breastfeeding impacts the timing of myelination, whole brain volume, cortical thickness, and white matter volume have all been found to be increased among children with longer durations of breastfeeding experience [ 33 , 37 39 ]. For example, in a cross-sectional design, Deoni et al [ 33 ] investigated white matter maturation from 10 months to 4 years of age and found a positive association between the duration of exclusive breastfeeding and the development of white matter tracts.…”
Section: Psychological Effects Of Breastfeeding In Childrenmentioning
confidence: 57%
“…Furthermore, this study reported that breastfeeding was associated with white matter in tracts commonly associated with higher-order cognition and socio-emotional functioning, including the superior longitudinal fasciculus [ 33 ]. Another critical follow-up study from the same group of researchers assessed changes in white matter volume in a longitudinal design [ 39 ]. In this study, breastfed children displayed a prolonged window of white matter development between 16 months and 2 years, resulting in an overall myelin increase detectable by 2 years of age that persisted through childhood.…”
Section: Psychological Effects Of Breastfeeding In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Opposed to our study, only basic intensity features (average lesion PD- and T2-intensities) have been employed. Other studies used advanced MR techniques, such as measuring myelin water fraction in white matter (Kitzler et al, 2018) or MR spectroscopy (Ion-Margineanu et al, 2017). While these methods can provide new insight into how MS patients can be assessed with MR imaging, they are not commonly used.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning has also been used in MS to distinguish MS patients from healthy controls (Yoo et al, 2018), different disease courses in MS patients (Ion-Margineanu et al, 2017; Zhao et al, 2017) and also to predict conversion in CIS patients. The latter was addressed by (Wottschel et al, 2015), who included clinical and basic lesion features, and by (Kitzler et al, 2018), who analyzed lesion myelination.…”
Section: Introductionmentioning
confidence: 99%